Correction of vaginal dysbiosis in mice caused by a film-forming strain Staphylococcus aureus, using bacteriophages and probiotics - Vorobey, E. S.; Voronkova, O. S.; Vinnikov, A. I. (Regulatory Mechanisms in Biosystems, 2017)
The complex use of bacteriophages and probiotics is a promising trend in improving prevention and treatment of gynecological lesions. Our study of their influence on the microflora was performed on the model of vaginal dysbiosis of white laboratory mice induced by introduction of a filmforming strain of Staphylococcus aureus. For correction of dysbiosis, staphylococcal bacteriophage liquid, piobacteriophage polyvalent, intesti-bacteriophage liquid and probiotic "Vahilak" were used. For the identification of the microflora of the reproductive tract, samples of biological material from the vagina were obtained by sterile cotton swab and plated on nutrient media to determine the nature and extent of growth of the cultures. The maximal effect was found to occur with the correctional complex "bacteriophage staphylococcal liquid – vahilak" that led to decrease of total microbial number to 4.77 × 104 CFU/ml and to the restoration of the ratio of aerobic to anaerobic bacteria 1 : 52 when indicators of the norm were 4,69 × 104 CFU/ml and 1 : 52. In this case, 24 hours after the last injection of the preparations the amount of microaerophilic and anaerobic lactobacilli had increased by 20.8 and 2.1 times respectively. The frequency of isolation of microaerophilic lactobacilli increased to 100%, and anaerobic – up to 70%. Also the number of staphylococci, streptococci, enterococci, bacilli and enterobacteria decreased by 30.1, 1.1, 1.5, 2.2 and 11.8 times respectively. Also, there was a decrease in the detection rate of enterococci, micrococci and enterobacteria by 10% and bacilli by 20% compared to the control dysbiosis. The number of anaerobic bacteria also underwent significant changes. Thus, the number of fusobacteria decreased by 33.2 times, peptococci – 2.3, peptostreptococci – 6.6 and Bacteroides – 7.9 times, which is almost consistent with indicators of the norm. In addition, the frequency of detection of peptostreptococci decreased by 10%. Therefore, it can be concluded that medical bacteriophages are active against lesions caused by able to film-forming staphylococci, in vivo, so they are appropriate to use in medical practice both independently and in combination with other agents.